Revitalisasi dan Identifikasi Nilai-Nilai Multikultural Pada Tradisi Lebaran Etnik Betawi di Kelurahan Cakung Barat, Kecamatan Cakung DKI Jakarta - Abdul Fadhil; Andy Hadiyanto; Ahmad ` Hakam; Amaliyah Amaliyah; Dewi Anggraeni (Penamas, 2019)
This research aims to describe multicultural values ​​in the Lebaran tradition of the Betawi community and the process of revitalizing multicultural values. The this time the attitude of empathy, tolerance, social solidarity, equality and justice began to reduce along with the fulfillment of biological needs and egocentric attitudes. Betawi people have a local tradition to be used as a standard for life, religion and community. The local traditions that continues to this day is the lebaran tradition or "celebrating Eid al-Fitr". The term lebaran is an acculturation of Javanese culture, Chinese, and Islam. The multicultural values ​​in the lebaran tradition of the Betawi community include: First accepting differences, is to allow people to visit without considering ethnicity, and religion and social strata. Second generous attitude, is to give food and drink to every guest who comes. Third empathy attitude, is forgive each other for family and neighbors. Conservation of the lebaran tradition is the obligation of the Betawi community and the regional government of DKI Jakarta. Revitalizing multicultural values ​​in the Lebaran tradition of the Betawi people. through: religious ceremonies, and the implementation of religious holidays. The revitalization factor are two: the motive of cause and achieving the goal.